Cystic Fibrosis Liver Disease: Outcomes and Risk Factors in a Large Cohort of French Patients - Boëlle, Pierre‐Yves (Hepatology, 2018)
Cystic fibrosis (CF)–related liver disease (CFLD) is a common symptom in patients with CF. However, its prevalence, risk factors, and evolution are unclear. We analyzed a large database of patients with CF to investigate the incidence of CFLD, its related risk factors, and the use and effect of ursodeoxycholic acid (UDCA) treatment. We retrospectively analyzed 3,328 CF patients with pancreatic insufficiency born after 1985 and recruited into the French CF Modifier Gene Study since 2004. We determined liver status, age at CFLD and severe CFLD onset, sex, CFTR genotype, history of meconium ileus, treatment with UDCA, and respiratory and nutritional status. The incidence of CFLD increased by approximately 1% every year, reaching 32.2% by age 25. The incidence of severe CFLD increased only after the age of 5, reaching 10% by age 30. Risk factors for CFLD and severe CFLD were male sex, CFTR F508del homozygosity, and history of meconium ileus. Increasingly precocious initiation of UDCA treatment did not change the incidence of severe CFLD. Finally, patients with severe CFLD had worse lung function and nutritional status than other CF patients. Conclusion: CFLD occurs not only during childhood but also later in the lifetime of patients with CF; male sex, CFTR F508del homozygosity, and history of meconium ileus are independent risk factors for CFLD development; earlier use of UDCA over the last 20 years has not changed the incidence of severe CFLD, leading to questions about the use of this treatment in young children given its possible adverse effects.